Hypothalamic–Pituitary–Adrenal Axis Dysregulation and Its Impact on Exercise Capacity and Recovery in Regularly Training Individuals - Gluzicka, Anna; Palacz, Bartosz; Teper, Maria Magdalena; Perz, Wiktor; Polus, Aleksander; Wrona, Julia Anna; Kubiś, Natalia Marianna; Olczyk, Liwia; Piotrowski, Jędrzej; Korolchuk, Anhelina; et al. (Quality in Sport, 2026)
Regular training imposes repeated physiological demands that activate neuroendocrine stress regulation, with the hypothalamic–pituitary–adrenal (HPA) axis playing a central role. Cortisol supports metabolic regulation and adaptation to exercise-related stress; however, prolonged exposure to high training loads combined with insufficient recovery may lead to functional alterations in HPA axis regulation, potentially affecting exercise capacity and recovery processes. This narrative review synthesizes current evidence on HPA axis dysregulation in regularly training individuals, with particular emphasis on its relevance for exercise capacity and recovery. The review includes peer-reviewed experimental, observational, longitudinal, and sport-specific studies addressing HPA axis physiology, cortisol secretion dynamics, cortisol awakening response (CAR), training load, fatigue, overreaching, overtraining, exercise capacity, and recovery in physically active populations. Available evidence indicates that cumulative training stress is associated with changes in basal cortisol secretion, diurnal cortisol rhythm, and CAR. Functional alterations in HPA axis activity may influence metabolic efficiency, neuromuscular function, stress responsiveness, and performance stability. These responses appear to occur along an adaptive–maladaptive continuum and are strongly modulated by individual characteristics, training structure, and recovery adequacy. Importantly, many training-related disturbances of HPA axis function seem to be time-dependent and at least partially reversible. Viewing HPA axis dysregulation as a dynamic and functional process may improve interpretation of training responses, while longitudinal assessment of cortisol-related markers, interpreted within the broader training and recovery context, may provide valuable insight into individual stress adaptability in regularly training individuals.